2023
DOI: 10.12688/f1000research.131518.1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary knowledge assessment among the patients with type 2 diabetes in Madinah: A cross-sectional study 

Abstract: Background: There is a huge burden of nutrition-related non-communicable diseases, and diabetes is one of the leading chronic nutrition-related diseases affecting more than 500 million people globally. Collecting information regarding the awareness of dietary and nutrition knowledge among diabetic patients is the first step to developing a disease prevention program. Thus, this study primarily aims at assessing the dietary awareness of diabetes patients attending the diabetic centre in Madinah governorate, Sau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…This review showed that high diet knowledge and skills were associated with healthy diet consumption and that female gender was associated with high diet knowledge. Another previous study found most participants showed an average level of dietary knowledge in general, as well as poor knowledge of carbohydrates, fat, and poor food choices [47]. Similarly, this review found inadequate diet knowledge and practices more common among men than women.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This review showed that high diet knowledge and skills were associated with healthy diet consumption and that female gender was associated with high diet knowledge. Another previous study found most participants showed an average level of dietary knowledge in general, as well as poor knowledge of carbohydrates, fat, and poor food choices [47]. Similarly, this review found inadequate diet knowledge and practices more common among men than women.…”
Section: Discussionsupporting
confidence: 65%
“…A study conducted on Asian, Middle-Eastern, and North African immigrants in Saudi Arabia showed they are more likely to engage in unhealthy diets, leading to compromised health [46]. Knowledge was also highlighted as another factor influencing dietary habits [4,47]. This review showed that high diet knowledge and skills were associated with healthy diet consumption and that female gender was associated with high diet knowledge.…”
Section: Discussionmentioning
confidence: 99%